2023
DOI: 10.1094/pdis-09-22-2164-re
|View full text |Cite
|
Sign up to set email alerts
|

Seed and Pollen Transmission of Tomato Leaf Curl New Delhi Virus, Tomato Leaf Curl Taiwan Virus, and Tomato Yellow Leaf Curl Thailand Virus in Cucumbers and Tomatoes

Abstract: Understanding the seed-borne nature of plant viruses is essential for developing disease control strategies and is impactful to the seed market. Here, we investigated seed transmissibility of tomato leaf curl New Delhi virus-cucumber isolate (ToLCNDV-CB) and -oriental melon isolate (ToLCNDV-OM) in cucumber and seed transmissibility of tomato leaf curl Taiwan virus (ToLCTV) and tomato yellow leaf curl Thailand virus (TYLCTHV) in tomato. Parent plants were inoculated using agroinfiltration with virus infectious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…With ToLCNDV, most reports that describe transmission through seeds have focused on the Asiatic strains of the virus [33][34][35][36]. Before the present work, only two research works had studied the seed transmission of ToLCNDV-ES in cucurbits, of which only one described that this mode transmission is possible in zucchini plants [37].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…With ToLCNDV, most reports that describe transmission through seeds have focused on the Asiatic strains of the virus [33][34][35][36]. Before the present work, only two research works had studied the seed transmission of ToLCNDV-ES in cucurbits, of which only one described that this mode transmission is possible in zucchini plants [37].…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, recent studies on tomato have reported the absence of TYLCV and tomato yellow leaf curl Sardinia virus (TYLCSV) transmission through infected seeds in tests performed at different locations [39,40]. Finally, the seed transmission of SPLCV was not detected after the recent large-scale screening of sweet potato plants [33][34][35][36]41]. The analysis of melon seedlings germinated from the ToLCNDV-ES-infected seeds did not support vertical transmission [42].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Some plant-infecting viruses, especially RNA viruses, have been identified in pollen, reviewed in Fetters and Ashman [ 29 ] and Mink [ 82 ]; thus, it is not surprising that many of these viruses are detected and identified from plant pollinators. Within the context of geminiviruses, there are only a handful of reports of the identification of viruses in the genus Begomovirus in floral parts including pollen and seeds [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. Thus, it is likely that we have sampled the apiscitlodal virus and nomiamastrel virus that are in floral tissue, including pollen, carried on the honeybee and solitary bees during pollination.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the experimental evidence shown was the amplification by PCR of Begomovirus genomes from the seeds of infected plants, and in some cases from the asymptomatic grow-out seedlings. ToLCNDV, ToLCTV, and TYLCTHV can be transmitted via seeds or pollens of cucumber and tomato plants to an extend of 70-77% (Chang et al, 2023). Pérez-Padilla et al (2020) reported that TYLCV-IL is seed-borne but is not seed transmitted in tomatoes or N. benthamiana, suggesting that transmission through seed is not a general property of TYLCV.…”
Section: Begomovirus Seed Transmissionmentioning
confidence: 99%